Hybrid nanomaterials for improved photocatalytic performance - Ho, Jeffrey Weng Chye. (2011)
Water pollutions have been an uprising issue worldwide. A promising solution is the use of photocatalyst whereby it converts the harmful organic compounds to water (H2O) and carbon dioxide (CO2). The redox reactions will regenerate continuously while the composition of the photocatalyst will remain unchanged. Till date, titanium dioxide (TiO2) is the most commonly used photocatalyst. However, due to wide bandgap (3.2 eV), it could only absorb Ultraviolet (UV) light. As such, it would be a great motivation to develop a new hybrid photocatalyst that aborbs both UV and visible light absorption. In this project, silver nanoparticles were loaded onto titanium dioxide (Ag-TiO2) surfaces through a 4-steps process. These steps are (i) hydrothermal treatment (ii) ion-exchange (iii) photoreduction and (iv) post-annealing. A total of 8 samples were prepared and it was found that Ag-TiO2 annealed at 350oC and above, exhibited both UV and visible light absorption. Among them, Ag-TiO2 450 degraded MO to colourless solution within 60 to 90 minutes under both UV and visible light. As such, Ag-TiO2 450 was used as a comparison with Degussa P25; a commercialized photocatalyst which is used in industries and research institutes. The data collected showed the degradation of MO solution with P25 is still the best under UV light. Although our sample did not degrade as fast as P25, the degradation performance is still comparable. Most importantly, we have an edge over P25 in term of visible light absorption. As such, this new finding does not only help to reduce the cost of production but also, to make it affordable.